2023
DOI: 10.1038/s41598-023-33537-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis and nomogram establishment and verification of brain astrocytoma patients based on SEER database

Abstract: Astrocytoma is a common brain tumor that can occur in any part of the central nervous system. This tumor is extremely harmful to patients, and there are no clear studies on the risk factors for astrocytoma of the brain. This study was conducted based on the SEER database to determine the risk factors affecting the survival of patients with astrocytoma of the brain. Patients diagnosed with brain astrocytoma in the SEER database from 2004 to 2015 were screened by inclusion exclusion criteria. Final screened brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is suggested that the column-line diagram has good predictive ability for the risk of secondary thyroid cancer in breast cancer patients 3 and 5 years after the onset of the disease. However, since the data were obtained from the United States, more studies are needed to verify whether the results obtained by applying this data can be applied to the Chinese population, and the results of this study can provide some references for clinicians [14] .…”
Section: Utility and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is suggested that the column-line diagram has good predictive ability for the risk of secondary thyroid cancer in breast cancer patients 3 and 5 years after the onset of the disease. However, since the data were obtained from the United States, more studies are needed to verify whether the results obtained by applying this data can be applied to the Chinese population, and the results of this study can provide some references for clinicians [14] .…”
Section: Utility and Discussionmentioning
confidence: 95%
“…The area under the ROC curve (AUC value) and C-index were used to evaluate the accuracy of the model, the AUC and C-index range from 0-1, the closer to 1 indicates that the model is more accurate, and it is usually considered that the model has a better predictive ability when the AUC reaches more than 0.7; the calibration curve was used to evaluate the degree of calibration of the model, and the closer the calibration curve is to the standard curve, the stronger the predictive ability of the model. Variables with a one-way COX regression of P < 0.1 were included in the multifactor analysis, and the multifactor analysis was included in the nal model with the criterion that the difference was considered statistically signi cant at P < 0.05 [14] .…”
Section: Grouping Methodologymentioning
confidence: 99%